India : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for India. (IMF Staff Country Reports; Country Report, 2018)
This 2018 Article IV Consultation highlights that stability-oriented macroeconomic policies and progress on structural reforms continue to bear fruit in India. Following disruptions related to the November 2016 currency exchange initiative and the July 2017 goods and services tax rollout, growth slowed to 6.7 percent in FY2017/18, but a recovery is under way led by an investment pickup. Headline inflation averaged 3.6 percent in FY2017/18, a 17-year low, reflecting low food prices on a return to normal monsoon rainfall, agriculture sector reforms, subdued domestic demand, and currency appreciation. Growth is forecast to rise to 7.3 percent in FY2018/19 and 7.5 percent in FY2019/20, on strengthening investment and robust private consumption.